Application of Humic Acid Isolated From Kalimatan Peat Soil Modifying Magnetite for Recovery of Gold (Jurnal Bahan Alam Terbarukan, 2019)
Humic acid modifying magnetite particles (Mag-HA) were developed for recovery of gold from chloride solution (HAuCl4). The Mag-HA particles were prepared by co-precipitation procedure with Fe(III) and Fe(II) chloride salts, sodium hydroxide, and humic acid. FTIR characterization for Mag-HA after modification indicated the presence of the specific absorption for functional groups of humic acid and Fe-O bonds, though with lower intensity. The Mag-HA particles exhibited a typical superparamagnetic characteristic with a saturation magnetization of 66.99 emu/g. The Mag-HA particles were applied for AuCl4- adsorption and results showed that the optimum adsorption of [AuCl4]- onto Mag-HA was found at pH 3. The adsorption kinetics can be described by a pseudo-second order equation and the adsorption isotherm of the Mag-HA particles agreed well with Langmuir adsorption equation. The maximum adsorbed amount of [AuCl4]- was 0.62 mmol/g and the XRD analysis confirms that the adsorption of Au(III) by Mag-HA was accompanied by the formation of elemental gold.